Virtualização (SDN e NFV) com ênfase em desempenho de rede - Teixeira, Everton Vinicius (2018)
Telecom companies are always searching to update their networks to increase the number of new customers and provide for them better services, for this purpose appeared technologies known as SDN (Software Defined Networking) and NFV (Network Functions Virtualization). This work aims to explain what and how are these technologies working and also to establish metrics for the conventional networks quality measurement and the NFV and SDN networks in order to make a comparison of their performance. The methodology used for this research was exploratory which objective is the question or the problem formulation, with threefold purpose: develop hypotheses, increase the familiarity of the researcher with an environment, fact or phenomenon, carry out a more precise future research or modify and clarify concepts. It will be possible to verify that SDN and NFV technologies can bring gains, mainly from a financial point of view, by using promising technologies, and evaluating conventional networks and using the metrics that will be described, we can put the verification as a main contribution that the SDN and NFV networks perform better than their predecessors, but with a high complexity and high implementation cost, but over the time this cost’s will be paid back trough a low OPEX (Operational Expenditure).